First Record of Pediobius pyrgo Walker (Hymenoptera: Eulophidae) in South America and its Emergence from Egg Sacs of Latrodectus geometricus C. L. Koch (Araneae: Theridiidae) - Karine Schoeninger; Diego Pádua; Lidianne Salvatierra; Marcio Oliveira (EntomoBrasilis, 2015)
We record the first time the occurrence of Pediobius pyrgo (Walker) (Hymenoptera: Eulophidae) for South America. This is also the first report of P. pyrgo emerging from egg sacs of Latrodectus geometricus C. L. Koch (Araneae: Theridiidae). Primeiro Registro de Pediobius pyrgo (Walker) (Hymenoptera: Eulophidae) na América do Sul e sua Emergência em Sacos de Ovos de Latrodectus geometricus C. L. Koch (Araneae: Theridiidae) Resumo. Registramos pela primeira vez a ocorrência de Pediobius pyrgo (Walker) (Hymenoptera: Eulophidae) para a América do Sul. Este também é o primeiro relato de P. pyrgo emergindo de sacos de ovos de Latrodectus geometricus C. L. Koch (Araneae: Theridiidae).